Micromanufacturing: A review—Part I. (September 2014) - Jain, VK; Sidpara, Ajay; Balasubramaniam, R; Lodha, GS; Dhamgaye, VP; Shukla, R
Micromanufacturing processes are expanding in their length and breadth as long as the related research and development (R&D) activities and applications are concerned. Products are getting miniaturized and their performance efficiency is getting enhanced by the addition of micro/nanofeatures and devices. In the set of these two articles (Part I and Part II), an attempt has been made to review the latest R&D activities of the selected micromanufacturing processes. This article (Part I) deals with a review of the literature related to attrition (subtractive, or machining and finishing) processes (both types—traditional and advanced) including microturning, micromilling, microdrilling, abrasive jet micromachining, laser beam micromachining, electrochemical micromachining, magnetorheological finishing, abrasive flow finishing, magnetic abrasive finishing, ion beam micromachining and so on. Apart from the subtractive processes, an overview of the X-ray lithography has also been presented. An attempt has been made to report some applications to help the readers to evolve more new applications of these processes. At the end of different sections/subsections, some research areas have been identified, which would hopefully fill the gaps between the theoretical analysis, experimental work and applications.